Mentoring in Teaching Education - Ludmila ARMASU-CANTIR; Nadiya KICHUK; Dora IVANOVA; Olena BILA; Olena BUKHNIEVA (ACROSS)
The modern educational space positions pedagogical mentoring as an essential component of the professional development support system for educational practitioners. The article analyzes leading trends in pedagogical education, revealing the role of mentoring as a powerful tool for enhancing teacher training for the 21st century in the context of the development of the innovative educational process in higher education.